Lipocalin-2 is involved in emotional behaviors and cognitive function - Ferreira, Ana C.; Pinto, Vitor; Mesquita, Sandro D.; Novais, Ashley; Sousa, Joao C.; Correia-Neves, Margarida; Sousa, Nuno; Palha, Joana A.; Marques, Fernanda (Frontiers in Cellular Neuroscience, 2013)
Lipocalin-2 (LCN2), an iron-related protein well described to participate in the innate immune response, has been shown to modulate spine morphology and to regulate neuronal excitability. In accordance, LCN2-null mice are reported to have stress-induced anxiety. Here we show that, under standard housing conditions, LCN2-null mice display anxious and depressive-like behaviors, as well as cognitive impairment in spatial learning tasks. These behavioral alterations were associated with a hyperactivation of the hypothalamic-pituitary-adrenal (HPA) axis and with an altered brain cytoarchitecture in the hippocampus. More specifically, we found that the granular and pyramidal neurons of the ventral hippocampus, a region described to be associated with emotion, were hypertrophic, while neurons from the dorsal hippocampus, a region implicated in memory and cognition, were atrophic. In addition, LCN2-null mice presented synaptic impairment in hippocampal long-term potentiation. Whether the LCN2 effects are mediated through modulation of the level of corticosteroids or through a novel mechanism, the present observations bring further into light this immune-related protein as a player in the fine-tuning of behavior and of synaptic activity.